SAT0074 Selectively antagonizing the EP4 prostanoid receptor significantly ameliorates pathological features in a rat model for inflammatory arthritis. (23rd January 2014) - Chiusaroli, R.; Ferrari, F.A.; Borriello, M.; Grotti, A.; Catapano, L.; Cavagnoli, R.; Lanza, M.; Stasi, L.P.; Rovati, L.; Caselli, G.
Abstract : Background: Recent studies highlight the role of the EP4 prostanoid receptor in promoting autoimmune inflammation via T helper cells, namely Th1 and Th17. Objectives: Aim of the present studies was to test CR6086, a selective antagonist at the EP4 receptor, for a potential activity in a widely recognized animal model for inflammatory arthritis. The Collagen Induced Arthritis (CIA) model in the Lewis rat was chosen. Methods: The effect of CR6086 was studied in a dose-response paradigm, and in comparison to the Jak3 inhibitor DMARD Tofacitinib and to naproxen. For each experiment, 60 Lewis male rats were immunized by intradermal injection at the base of the tail of an emulsion containing 150 ug bovine collagen type II in complete Freund's adjuvant (CFA), or were injected with incomplete Freund's adjuvant (sham group). Three weeks after the first immunization, the same animals were boosted with the same method. Three days after booster injection, arthritis had developed in all animals, but not in the sham-injected; edema was assessed and the animals were then randomized and assigned to treatment groups (n=12). Treatments were thus started in a true curative protocol, after genuine arthritis had already developed, and were performed for 14 days. All compounds were administered orally. The doses of CR6086 were 1.5 mg/kg/b.i.d. and 15 mg/kg/b.i.d., or 15 mg/kg/o.a.d. Edema measurement was performed again after 7 and 14 days of treatment, and then all animals were blindly scored for clinical signs of arthritis (redness, swelling, pain of hindlimb joints) and sacrificed. Hind paws were explanted and processed for histology. At least three non-consecutive sections for each paw were blindly scored at the level of tarsus, metatarsus and calcaneus for the following histological features: edema; synovial hyperplasia (pannus); inflammatory cell infiltrate; cartilage damage; bone erosion; periosteal osteogenesis. Statistical analysis was performed with ANOVA followed by Dunn's or Holm-Sidak tests comparing all treatment groups vs. vehicle. Results: After 7 days of treatment, edema was significantly reduced in CR6086-treated groups at both doses, compared to vehicle. After 14 days of treatment, CR6086 15 mg/kg/b.i.d. completely abated the edema, while CR6086 1.5 mg/kg/b.i.d. significantly reduced the edema by over 60%. In all experiments, administration of CR6086 was associated with a profound, dose-dependent decrease of the arthritis clinical score compared to vehicle. All histological features of arthritis were significantly and dose-dependently ameliorated following treatment with CR6086. In later experiments, we observed that a dose of 15 mg/kg o.a.d. of CR6086 was sufficient to ensure maximum efficacy. Tofacitinib also showed dose-dependent efficacy in the CIA model, however with lower potency and a need for b.i.d. administration, likely due to the PK profile of the compound. Naproxen was active on inflammatory parameters, at the same doses as CR6086. Conclusions: In conclusion, in a widely accepted animal model for inflammatory arthritis, in a curative protocol CR6086 demonstrated very good efficacy in all parameters examined, including edema, clinical arthritis score, and histological features. Disclosure of Interest: None Declared